Estratégias de design sustentável para a valorização dos recursos locais a partir do estudo da cadeia do babaçu no município de Itapecuru Mirim - Viegas, Valquíria Aires (2015)
Brazil possesses a wealth of natural resources, however part of the population, even living near these resources, has a low quality of life. This same context can be perceived in Maranhão. The state has diverse vegetation composed of the Amazon Forest, savanna, mata dos cocais (coconut wooded region), swamps and the second largest coast in the country with immense marine biodiversity. However, the state of Maranhão has the municipalities with the lowest Municipal Human Development Index (MHDI). In this context, the dissertation directs the perspective to Sustainable Design seeking to understand which Project strategies can stimulate the valorization of local resources and the form in which such strategies can be understood and applied to lead product development, services and sustainable communication in a Maranhense context. The hypothesis of this research is that Design possesses tools and the capacity to stimulate and increase local activities, and from this point, improve people’s quality of life. The research was carried out in three stages: Theoretical Foundation composed of bibliographical and documental research; Intensive Direct Observation which combined simple and contextual observation with structured and semistructured interviews; and finally, Qualitative Analysis of data obtained in these stages using the babaçu coconut productive chain in the Itapecuru Mirim micro-region in Maranhão as demarcation. As a result of this study, relations were establishe between Design management levels, the main obstacles in the babaçu cocnut productive chain and sustainable design strategies that favor the valorization and promotion of local resources in Maranhão.